Ecotoxicological tests with cadmium and chromium using postlarvae of silverside Odontesthes (Austromenidia) regia regia Hildebrand - Vera, Giovana (2001)
In the present paper, the mean effective concentrations (EC50%) of cadmium (Cd+2) and chromium (Cr+6) using postlarvae of the silverside fish Odontesthes (Austromenidia) regia regia were determined. The postlarvae were exposed to different concentrations of the metals, between 0,142 and 1,208 mg.L–1 of cadmium and between 0,53 and 33,74 mg.L–1 of chromium. The mean effective concentrations (EC50%) obtained were 0,648 mg.L–1 of cadmium (at 96 h) and 2,68 mg.L–1 of chromium (at 96 h). Comparatively, cadmium is more toxic than chromium, and silverside is more tolerant than other organisms.